Fishmeal replacement with Spirulina Platensis and Chlorella vulgaris in African catfish (Clarias gariepinus) diet: Effect on antioxidant enzyme activities and haematological parameters - Raji, Ameenat Abiodun; Alaba, Peter Adeniyi; Yusuf, Hindatu; Abu Bakar, Noor Hidayati; Mohd Taufek, Norhidayah; Muin, Hasniyati; Alias, Zazali; Milow, Pozi; Razak, Shaharudin Ab (Elsevier, 2018)
This study explored fishmeal replacement with two freshwater microalgae: Spirulina Platensis and Chlorella vulgaris in African catfish (Clarias gariepinus) diet. The effect of inclusion of the two microalgae on biomarkers of oxidative stress, haematological parameters, enzyme activities and growth performance were investigated. The juvenile fish were given 3 distinct treatments with isonitrogenous (35.01–36.57%) and isoenergetic (417.24–422.27 Kcal 100 g−1) diets containing 50% S. platensis (50SP), 75% S. platensis (75SP), 50% C. vulgaris (50CL), 75% C. vulgaris (75CL) and 100% fishmeal (100% FM) was used as the control diet. The result shows that all the diets substituted with both S. platensis, and C. vulgaris boosted the growth performance based on specific growth rate (SGR) and body weight gain (BDWG) when compared with the control diet. The feed conversion ratio (FCR) and protein efficiency ratio (PER) was significantly influenced by all the supplementations. The haematological analysis of the fish shows a significant increase in the value of red and white blood cells upon supplementation with 50SP and 50CL but decrease slightly when increased to 75SP and 75CL. Furthermore, the value of haematocrit and haemoglobin also increased upon supplementation with 50SP and 50CL but decrease slightly when increased to 75SP and 75CL. The white blood cell (WBC), red blood cell (RBC) increased, while total cholesterol (TCL), and Plasma glucose levels decreased significantly upon supplementation of algae. This is a clear indication that S. platensis and C. vulgaris are a promising replacement for fishmeal, which is a source protein in the C. gariepinus diet.